A Review Unveiling the Ferroptosis-Regulated Cell Signalling Pathways in Breast Cancer to Elucidate Potent Targets for Cancer Management - Pandey, Pratibha; Pandey, Shivam; Ramniwas, Seema; Ballal, Suhas; Kumar, Sanjay; Bhat, Mahakshit; Sharma, Shilpa; Kumar, M. Ravi; Khan, Fahad (Current Pharmaceutical Design, 2025)
Recent research suggests that targeting ferroptosis exhibits promise as a potent treatment approach for breast carcinoma. Specific subtypes of tumor cells exhibit heightened vulnerability to ferroptosis-inducing chemicals, which selectively trigger tumor stem cells' demise, enhance tumor cells' sensitivity to chemotherapeutic drugs, and eliminate cancerous cells. Ferroptosis plays a dual role in breast cancer progression, emerging as both a stimulating and inhibitory component. Ferroptosis is effective in treating cancer cells (mesenchymal breast), identified by their ability to undergo Epithelial-mesenchymal Transition (EMT) and their resistance to conventional therapies. Pharmaceutical drugs that hinder the activity of enzymes known as kinases, which are involved in the Akt/mTOR/PI3K signaling pathway, have shown significant potential in the treatment of breast carcinoma. This review investigates the molecular mechanisms of different signaling pathways implicated in ferroptosis in breast carcinoma, with specific emphasis on metastasis, invasion, and proliferation. Our study contributes to understanding a potentially important target that could be used in developing therapeutic strategies for breast cancer treatment.
Keywords: EMT